Случај атипичне интерференције ИгА парапротеина на вишеструким хемијским тестовима: како се носити с тим - Sarkar, Rajarshi (Journal of Medical Biochemistry, 2024)
Background: This case report discusses how paraproteins interfere with multiple chemistry analyses and protocols to overcome such obstacles. Case Report: A serum specimen containing two monoclonal IgA (λ – light chain) paraproteins is subjected to a battery of tests on three wet chemistry platforms – AU5800, Cobas Pure and Alinity ci; results were compared with those on a Vitros 350/ ECiQ dry chemistry platform. Paraprotein interference was found to affect the bilirubins, inorganic phosphate and iron, whose repeat runs were also found to be irreproducible. Dilution with normal saline also failed to produce a satisfactory effect. Deproteinization by polyethylene glycol and dilution of the specimen with a normal serum specimen were observed to produce desirable results. Conclusion: Interference by IgA paraprotein on measurement of the bilirubins, phosphate and iron in the wet chemistry system can be mitigated either by deproteinization or by dilution with a normal serum.